Rekognisi Axel Honneth: Gramatika Moral Bagi Defisit Rasionalitas Beragama - Meitikasari, Diah; Drianus, Oktarizal (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2021)
This paper aims to explore Axel Honneth's thoughts on recognition. This is considered important that today, religious moderation is expected to be a mode of living together that able to reconstructs a just and rational moral grammar, instead of falling into a deficit of rationality. This paper uses a literature study approach with the main source of Honneth's work, The Struggle for Recognition: Moral Grammar for Social Conflict. Several points were learned, namely: 1) recognition for Honneth is a normative basis for recognition and social struggle that eliminates all forms of disrespect; 2) Honneth's Recognition manifests in three domains: love, rights, and solidarity; 3) Mutual relations in three domains which are basic self-confidence, self-respect, and self-esteem; 4) Honneth's recognition can be a moral grammar for religious moderation efforts in Indonesia.